3PC-005 Physicochemical stability of cefazolin in polypropylene syringes and in elastomeric devices. (24th March 2020) - D'huart, E; Sobalak, N; Vigneron, J; Charmillon, A; Demore, B
Abstract : Background and importance: Cefazolin is an antibiotic used to treat methicillin susceptible Staphylococcus aureus infections. The usual dose of cefazolin is 6 g/day. For β-lactam antibiotics, studies have demonstrated that continuous administration is the preferred mode of administration. To the best of our knowledge, no stability data for cefazolin solutions at 125 mg/mL (6 g in 48 mL) in syringes or at 50 mg/mL (12 g in 240 mL) in elastomeric devices have been published. Aim and objectives: The objectives were to study the stability of cefazolin solutions (1) at 125 mg/mL, diluted in 0.9% sodium chloride (0.9% NaCl) or 5% dextrose (D5W), in polypropylene syringes at 20–25°C and (2) at 50 mg/mL, in the two solvents, in elastomeric devices at 37°C, after preparation and after storage for 6, 24 and 48 hours. Material and methods: Three preparations for each condition were made. For each analysis, three samples from each preparation were taken and analysed by high performance liquid chromatography coupled with a photodiode array detector. The method was validated according to the International Conference on Harmonisation Q2 (R1). Physical stability was evaluated by visual and subvisual inspection (turbidimetry by UV spectrophotometry, as recommended by the European Consensus Conference). pH values were measured. Results: For each solvent, cefazolin solutions at 125 mg/mL and at 50 mg/mL retained more than 90% of the initial concentration after 48 hours. During the study, pH values increased with the addition of more than 1 pH unit after 48 hours at 125 mg/mL and after 6 hours at 50 mg/mL. Absorbance values were rapidly modified for solutions stored in elastomeric devices and were stable for solutions in syringes up to 24 hours. Conclusion and relevance: In view of the results and despite the fact that solutions retained more than 90% of the initial concentration, we propose to limit the stability of cefazolin in 0.9% NaCl and D5W at 125 mg/mL to 24 hours in polypropylene syringes at 20–25°C. These stability data of concentrated solutions provide additional knowledge in performing continuous infusion of cefazolin in polypropylene syringes. In elastomeric devices, cefazolin solutions at 50 mg/mL stored at 37°C were unstable after 6 hours. These preparations are not recommended. References and/or acknowledgements: No conflict of interest.